2018
DOI: 10.1021/acs.macromol.7b01979
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of Cross-Linked Polymers with Complex Cure Pathways: A Case Study of Bismaleimide Resins

Abstract: To date, molecular modeling of cross-linking polymers has focused on those involving single-reaction cure mechanisms, such as epoxies and the epoxide–amine reaction. In this work, we have developed a novel cross-linking framework that is capable of undertaking complex cure mechanisms involving several simultaneous reaction pathways with minimal user input. As a case study, a bismaleimide (BMI) resin is considered herein which possesses multiple cure reactions and reaction pathways. Using an adaptable molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 58 publications
1
66
0
Order By: Relevance
“…(1) Cross-linking and Monte-Carlo or molecular dynamics simulations using a coarse-grained model and then conversion back to the original atomistic description [8][9][10][11] (2) Starting with a stoichiometric mixture of the epoxy monomer and the hardener and then "polymerizing" the mixture in conjunction with atomistic molecular dynamics (MD) simulations. This method has also proven effective for complex cross-linking reactions [12] The most extensive research effort is found in the polyepoxy systems EPON 862 resin cross-linked with diethyltoluenediamine (DETDA) [13][14][15][16] and triethylenetetramine (TETA) [17][18][19][20] because of their wide use in the fields of modern aeronautics and composite materials and their use in the development of micro-and nanodevices with desired properties. The cross-linking of the diglycidyl ether of bisphenol-A (DGEBA) resin was also widely studied with different hardeners, i.e., isophorone diamine (IPD) [21,22], trimethylene glycol di-p-aminobenzoate (TMAB) [23], DETDA [24], diaminodiphenyl sulfone (DDS) [9], methylenedianiline [25], poly(oxopropylene) diamines (POP) [26,27], 4,4 ′ -methylenebis(cyclohexylamine) (MCA) [26], diethylenetriamine (DETA) [28], and JEFFAMINE® D-230 [29].…”
Section: Introductionmentioning
confidence: 99%
“…(1) Cross-linking and Monte-Carlo or molecular dynamics simulations using a coarse-grained model and then conversion back to the original atomistic description [8][9][10][11] (2) Starting with a stoichiometric mixture of the epoxy monomer and the hardener and then "polymerizing" the mixture in conjunction with atomistic molecular dynamics (MD) simulations. This method has also proven effective for complex cross-linking reactions [12] The most extensive research effort is found in the polyepoxy systems EPON 862 resin cross-linked with diethyltoluenediamine (DETDA) [13][14][15][16] and triethylenetetramine (TETA) [17][18][19][20] because of their wide use in the fields of modern aeronautics and composite materials and their use in the development of micro-and nanodevices with desired properties. The cross-linking of the diglycidyl ether of bisphenol-A (DGEBA) resin was also widely studied with different hardeners, i.e., isophorone diamine (IPD) [21,22], trimethylene glycol di-p-aminobenzoate (TMAB) [23], DETDA [24], diaminodiphenyl sulfone (DDS) [9], methylenedianiline [25], poly(oxopropylene) diamines (POP) [26,27], 4,4 ′ -methylenebis(cyclohexylamine) (MCA) [26], diethylenetriamine (DETA) [28], and JEFFAMINE® D-230 [29].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Scheme , during the curing process of EG‐BMI resins, the major reactions were ene reaction and styrene–maleimide copolymerization reaction. Meanwhile, self‐polymerization and Diels–Alder reaction also happened in the systems . It was worth noting that it was previously thought that the ene reaction was succeeded by a Diels–Alder reaction between the newly formed di‐ene (from benzene ring of eugenol) and electron‐poor dienophile in maleimides.…”
Section: Resultsmentioning
confidence: 94%
“…DPBM reacted with the aromatic allyl compounds [44,45,51] like diallylbisphenol A DABPA, dipropargylether of bisphenol A DPBPA and Bis (propenyl phenoxybenzophenon) BPPB via Diels Alder reaction. A recent publication [15]…”
Section: Reaction Of Dpbm With Diallybisphenol a Via Diels Alders Reamentioning
confidence: 99%